CRITICAL ISSUES IN FOSTERING YOUNG LEARNERS’ LISTENING AND SPEAKING SKILLS IN PUBLIC SCHOOLS OF UZBEKISTAN - Tursunova, Dilfuza (Журнал иностранных языков и лингвистики, 2021)
This article discusses current critical issues related to listening and speaking skills of young learners in the process of teaching, in Uzbekistan. The picture that emerges concerning the current issues in listening and speaking to young learners can be given under two main headings: teacher-related issues and curriculum related issues.